Dr. Fraser Macintosh Rose, OBE, MB ChB (Edin), FCGP (1897–1972) co-founder of the Royal College of General Practitioners. (August 2019) - Timmis, Christopher
Fraser Rose was a general practitioner in Preston, Lancashire, England and a medical politician. He was one of two doctors who in 1951 took the initial steps and subsequently played a major role in the founding of the College of General Practitioners, later to become the Royal College of General Practitioners. This paper examines his life, his career in general practice and medical politics, and his unique contribution to the 'Steering Committee' that set up the College.